Virtual Interviewing Tips for the Otolaryngology Match Cycle During the COVID-19 Pandemic - Cristel, Robert T. (OTO Open, 2021)
Virtual interviews are planned for the upcoming 2020-2021 residency cycle. This presents a unique challenge for medical students. Due to the importance of the interaction of applicants and interviewers during the interview, medical students should thoroughly prepare for the upcoming virtual interview season. We offer practical and realistic concepts and techniques to optimize their interview experience. Technology and audiovisual equipment should be adjusted and enhanced to minimize video conferencing application errors and interview downtime. The applicant’s interview environment should focus on proper lighting, background, camera angles, and minimizing unwanted distractions. Mock interview sessions are invaluable to applicants and provide the opportunity to simulate the interview, refine their technology, adjust their environment, and become more comfortable in a virtual interview setting. These actions will prevent unnecessary disruptions and increase the focus of the interview toward the communication between the applicant and the interviewer.